Label-Free Proteomic Analysis of Smoke-Drying and Shade-Drying Processes of Postharvest Rhubarb: A Comparative Study - Liang, Wei; Chen, Yuan; Li, Xia; Guo, Fengxia; Sun, Jiachen; Zhang, Xuemin; Xu, Bo; Gao, Wenyuan (Frontiers in Plant Science, 2021)
Post-harvest processing plays a very important role in improving the quality of traditional Chinese medicine. According to previous studies, smoke-drying could significantly promote the accumulation of the bioactive components and pharmacological activities of rhubarb, but so far, the molecular mechanism hasn't been studied yet. In this research, to study the molecular mechanisms of post-harvest processing for rhubarb during shade-drying and smoke-drying, label-free proteomic analyses were conducted. In total, 1927 differentially abundant proteins (DAPs) were obtained from rhubarb samples. These DAPs were mainly involved in response and defense, signal transduction, starch, carbohydrate and energy metabolism, and anthraquinone and phenolic acid biosynthesis. Smoke-drying significantly enhanced the expression of proteins involved in these metabolic pathways. Accordingly, the molecular mechanism of the accumulation of effective ingredients of rhubarb was clarified which revealed the scientific evidence for this traditional process of smoke-drying has been used till now, and also provided a theoretical basis for the development of modern rhubarb drying methods.